Redefining Shadow Puppets Performed by Solo Raya Female Puppeters on YouTube - Setyasih Harini; Christy Damayanti; Qonitah Rohmadiena (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2026)
The research aims at exploring how female puppeteers from Solo Raya use YouTube to introduce shadow puppets to the wider world, focusing on their role as custodians of Javanese culture online. It underscores their pivotal role as custodians of Javanese culture in the digital realm, where female puppeteers meticulously safeguard and reinterpret shadow puppet traditions on YouTube, ensuring the enduring legacy of moral narratives, philosophical depth, and artistic intricacies for both local communities and international viewers. Using a feminist research design informed by post-feminist theory and citizen diplomacy, the findings are based on data from 14 female puppeteers, who served as key informants, collected via YouTube. Female puppeteers deliver traditional shadow puppet performances, challenging male-dominated narratives and empowering women in cultural transmission. This research continues to consider YouTube's role in enabling female puppeteers to speak back against earlier male-dominated narratives while also changing who performs. Results show that these women puppeteers, through the YouTube platform, cultivate widespread global appreciation for Javanese culture, advancing gender equity within traditional performing arts, and significantly enhancing Indonesia's national soft power.